2013
DOI: 10.1186/1472-6947-13-58
|View full text |Cite
|
Sign up to set email alerts
|

A study of general practitioners’ perspectives on electronic medical records systems in NHSScotland

Abstract: BackgroundPrimary care doctors in NHSScotland have been using electronic medical records within their practices routinely for many years. The Scottish Health Executive eHealth strategy (2008-2011) has recently brought radical changes to the primary care computing landscape in Scotland: an information system (GPASS) which was provided free-of-charge by NHSScotland to a majority of GP practices has now been replaced by systems provided by two approved commercial providers. The transition to new electronic medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 31 publications
1
42
0
1
Order By: Relevance
“…In the current study, participants who were aged 40 years and less, 20(15.3%)preferred a paper based medical record compared to those who were above 40 (28.2%) preferred paper based. documents" (P4).The current study of the implementation of an EMR was also supported by (Bouamrane & Mair, 2013)). This study reported that general practitioners' perspectives on electronic medical records systems in NHS Scotland felt their EMR system improved the record keeping This current research study of the OpenClinc EMR has not only improved the efficiency but also the quality of health care delivery with in Rwanda.…”
Section: Demographic Characteristicsmentioning
confidence: 66%
“…In the current study, participants who were aged 40 years and less, 20(15.3%)preferred a paper based medical record compared to those who were above 40 (28.2%) preferred paper based. documents" (P4).The current study of the implementation of an EMR was also supported by (Bouamrane & Mair, 2013)). This study reported that general practitioners' perspectives on electronic medical records systems in NHS Scotland felt their EMR system improved the record keeping This current research study of the OpenClinc EMR has not only improved the efficiency but also the quality of health care delivery with in Rwanda.…”
Section: Demographic Characteristicsmentioning
confidence: 66%
“…However, Bru-HIMS end-users were given training in functions that were not needed in the dental department, and they struggled to get appropriate technical training and support from the vendor -a problem that appears to be frequent with HIS implementation despite its impact in potentially improving the experience of clinicians [92,46,93].…”
Section: Yh Sidek Jt Martins I N T E R N a T Io N A L J O U R N mentioning
confidence: 99%
“…A recent review [34] of 9 years of EHR studies found the majority of EHRs have had very limited to negative impact on clinical workflow, and documenting improvements is difficult. Other recent reviews of studies, such as [29] which analyzed 12 years of EHR data, or [5] which looked at semi-structured interviews with physicians, concluded that there is not yet evidence of a clear impact of EHRs on clinical outcomes. Although interesting and clearly showing that there is work to do, the reports are too vague to point to where the problems may lie.…”
Section: Related Workmentioning
confidence: 97%
“…SMI RED-m eye tracker. 5 The RED-m is a remote eye tracker, that along with an Epiphan DVI-2-USB3.0 frame grabber, provides us with screen capture and corresponding tracking metrics to indicate where our participants were looking on their computer screen while interacting with the EHR. Standard eye trackers (including the SMI RED-m) provide solutions to track gaze directed to the screen of a dedicated portable computer.…”
Section: Data Collection Infrastructurementioning
confidence: 99%
See 1 more Smart Citation